Dynamical pathways of Antarctic Bottom Water in the Atlantic - Stephens, J; Marshall, D (2000)
A reduced-gravity model is developed to represent the flow of Antarctic Bottom Water (AABW) over realistic bathymetry in an Atlantic domain. The dynamics are based on the steady, planetary-geostrophic, shallow-water equations, including a linear bottom friction and a uniform diapycnal upwelling through the top of the model layer. The model solutions are broadly consistent with observations of the distribution and transport of AABW. The flows occur predominantly along potential vorticity contours, which are in turn broadly oriented along bathymetric contours. The characteristic weak flow across potential vorticity contours of the Stommel-Arons model is present as a small addition to this stronger forced mode along potential vorticity contours. As a consequence, mass balance is maintained not by hypothesized western boundary currents as in the Stommel-Arons model, but by the interplay between topographic slope currents and interior recirculations. In particular, a transposition is found in the flow of AABW from the western side of the Brazil Basin south of the equator to the western flank of the Mid-Atlantic Ridge north of the equator. This is also consistent with an analytical result derived by extending the Parsons mechanism to an abyssal layer overlying arbitrary bathymetry. The authors suggest that the results provide a more convincing zero-order picture than the Stommel-Arons model for the circulation of AABW and perhaps for abyssal water masses in general.